Analysis Optimation Algorithms at Shortest Path in Area Surabaya - Mas Nurul Hamidah (Fakultas Teknik Universitas Bhayangkara, 2016)
The shortest path is one case that often in mobile applications now, and there are several optimization algorithms supporting solution shortest path, it can use the greedy algorithm and the dynamic programming algorithms , of course, both of them have optimization methods are different, the case studies will be taken is the area around Surabaya which will evaluate the performance of the optimization algorithm at a certain point in the point area of Surabaya, the calculation by the two algorithms are, it will conclude appropriate optimization algorithm to get to certain areas in Surabaya area. From the evaluation results of two optimization algorithms are greedy and dynamic programming in the can the optimum solution is to distance the RSI jemur sari heading RSAL is solution the same optimum passed node A-C-E-G-H with total shortest distance that is 1.99 km, while the optimum solution royal plaza toward marvell city also same produces result between greedy algorithm and dynamic programming algorithms that is 1-2-5-7-9 with total cost 2,57 km shortest distance.